2004
DOI: 10.4049/jimmunol.172.9.5616
|View full text |Cite
|
Sign up to set email alerts
|

Enteric Nematodes Induce Stereotypic STAT6-Dependent Alterations in Intestinal Epithelial Cell Function

Abstract: Infection with gastrointestinal nematodes exerts profound effects on both the immune and physiological responses of the host. We showed previously that the Th2 cytokines, IL-4 and IL-13, induce STAT6-dependent changes in intestinal epithelial cell permeability, absorption, and secretion that are similar to those observed in a secondary infection with Heligmosomoides polygyrus. In the current study we investigated whether nematode-induced effects on epithelial cell function were 1) generic, 2) dependent upon ST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
105
1
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 92 publications
(118 citation statements)
references
References 41 publications
10
105
1
2
Order By: Relevance
“…Helminth-induced alterations in epithelial cell function and smooth muscle contractility in the small intestine are STAT6-dependent (11,14,15) and are mimicked by exogenous IL-4 and IL-13, indicating that these effects are due in part to activity at the type 2 receptor. Studies of the exogenous administration of IL-4 or IL-13 reveal that these cytokines have remarkably similar effects on sodium-linked glucose absorption and tissue permeability, but that there are also several differences, such as the prosecretory effects of IL-4 in the small intestine, which are mast cell-dependent and are not shared by IL-13 (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Helminth-induced alterations in epithelial cell function and smooth muscle contractility in the small intestine are STAT6-dependent (11,14,15) and are mimicked by exogenous IL-4 and IL-13, indicating that these effects are due in part to activity at the type 2 receptor. Studies of the exogenous administration of IL-4 or IL-13 reveal that these cytokines have remarkably similar effects on sodium-linked glucose absorption and tissue permeability, but that there are also several differences, such as the prosecretory effects of IL-4 in the small intestine, which are mast cell-dependent and are not shared by IL-13 (16).…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports showed that the dominant profile of cytokines is a major determinant of gut function in parasite infection (11,(13)(14)(15). There is evidence for both direct actions on effector cells, such as smooth muscle cells, epithelial cells, and enteric neurons, as well as indirect effects mediated by other immune or nonhemopoietic cells (11,(13)(14)(15)(16)(17). The interaction of Th2 cytokines and the receptor components, however, is not well understood and the mechanisms by which cytokines exert their functional effects in the gut remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Of interest therefore, are the immune-mediated changes in gut function that promote pathogen clearance, particularly in the context that may contribute to their ability to migrate, adapt, and survive host defenses. Nematodes that preferentially infect the small intestine induce a stereotypic and STAT6-dependent increase in permeability 52,53 that is mimicked by exogenous IL-13 administration. 51 The increased permeability facilitates exposure of worm products to resident immune cells.…”
Section: Role Of the Immune System In The Response To Pathogensmentioning
confidence: 99%
“…These effects are not observed in STAT6-, IL-4-, or IL-13-deficient mice resulting in impaired clearance of nematodes. [50][51][52][53] It is important to note that receptors for IL-4/IL-13 as well as STAT6 are expressed both on immune cells and epithelial cells, allowing for direct effects of these cytokines. 28 Thus, changes in receptor expression are important in controlling epithelial cell function in nematode infection.…”
Section: Role Of the Immune System In The Response To Pathogensmentioning
confidence: 99%
“…The IL-4R␣ chain pairs either with the common gamma chain (␥c) to form the type 1 IL-4R (for IL-4 binding) or with the IL-13R␣1 chain to form the type 2 IL-4R (for IL-4 and IL-13 binding). These cytokines can modulate the function of bone marrow-derived cells (T, B, NK, macrophage) and nonhematopoietic lineages, such as endothelium, 9 intestinal epithelial cells, 10 and smooth muscle. 11 Indeed, nonbone marrow cell-derived IL-4R␣ expression drives airway inflammation 12 and is required for expulsion of gastrointestinal helminths.…”
mentioning
confidence: 99%